P-B26 Changes in plasma BLyS levels in patients with HCV mixed cryoglobulinemic vasculitis during treatment with Rituximab. (January 2016) - Comstock, Emily; Emmanuel, Benjamin; Sneller, Michael; Kottilil, Shyamasundaran
Abstract : Background: Mixed Cryoglobulinemic Vasculitis (MC) is a known complication of chronic hepatitis C virus (HCV) infection, characterized by monoclonal expansion of IgM secreting B cells. B-lymphocyte Stimulator (BLyS), a member of the tumor-necrosis-factor super family of ligands, is an essential in vivo regulator of B cell homeostasis. High levels of BLyS have been observed in several autoimmune B cell mediated diseases. In this study, we evaluated plasma BLyS levels in patients with HCV-MC before, during, and after treatment with rituximab (RTX) compared with normal volunteers (NV). Methods: We treated patients with HCV-MC with 4 cycles of IV RTX (375 mg/m 2 ) and followed for response for an additional year. Plasma samples were tested for the levels of BLyS using ELISA from patients with HCV-MC (N = 14) before (day 0), during RTX treatment (month 1, 4), during full recovery (month 8), and from normal volunteers (NV) (N = 8). ANOVA was used for statistical comparisons on the levels of BLyS between the different groups. Result: Plasma BLyS levels were elevated among patients with HCV-MC (Mean 1.12 ± 0.4 ng/mL) when compared with NV (Mean 0.67 ± 0.1 ng/mL). Among patients with HCV- MC, plasma BLyS levels increased at one month post treatment with RTX (Mean 3.6 ± 0.6 ng/mL, P = 0.03). In patients with HCV-MC, BLyS levels were inversely correlated with B cell counts (r = −0.81, p2 ng/mL at month 8 in 4/6 patients who either had a relapse or did not achieve remission. Conclusions: BLyS levels are elevated in patients with B cell autoimmunity, such as HCV-MC. In patients with HCV-MC, persistently high levels of BLyS were observed in those who relapsed following RTX, thus suggesting a pathogenic role for BLyS in HCV-MC. These results provide a rationale for targeting BLyS, along with B cell depletion therapies, as a novel approach for the management of HCV-MC.